An investigation of the financial and psychological impact of COVID-19 on students at the University of the Witwatersrand, South Africa - Maepa, Pontsho (University of the Witwatersrand, Johannesburg, 2024)
The 2019 Coronavirus (COVID-19) intensified poverty, hunger, and health problems while having severe effects on sustainability measures. People faced psychological and financial difficulties because of the financial hardship caused by the pandemic.This study explored the financial and psychological impact of the COVID-19 pandemic among students on students from the University of the Witwatersrand, South Africa. A case study design was employed in this investigation. Ten (10) full-time University of Witwatersrand students, ages 18 to 30, were chosen using a purposive sampling technique. Individual interviews using a semi-structured interview guide were used to gather the data. The study found that while some participants reported minimal financial impact and effective coping strategies, others faced challenges with accommodation deposits, National Student Financial Aid Scheme (NSFAS) delays, and psychological distress. The study identified a range of emotional responses, including anxiety and academic concerns. Moreover, the transition to online learning presented both benefits and drawbacks, influencing students' academic performance and engagement. The study recommends considering the financial implications of accommodation deposits, ensuring timely disbursement of NSFAS allowances, and emphasizing interactive elements in online learning. Acknowledging the psychological toll, universities are urged to enhance mental health support services. Future pandemic responses should prioritise maintaining a supportive residential environment for students.
A research report Submitted in fulfillment of the requirements for a Master of Arts in the field of Social Development, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Coronavirus disease (COVID-19); pandemic; psychological; financial; students.; SDG-4: Quality education; SDG-3: Good health and well-being